Immunophenotyping and cytokine gene expression in experimental intramammary infection with staphylococcal species in mice - KRISHNAMOORTHY, P; SATYANARAYANA, M L; SHOME, B R; ROY, P (The Indian Journal of Animal Sciences, 2019)
Immunophenotyping and proinflammatory cytokine gene expression in mice mammary gland inoculated with Staphylococcus epidermidis, S. chromogenes, S. haemolyticus and S. aureus isolated from bovine milk were studied. Swiss albino mice were inoculated with 50 μl (2×104 CFU organisms) per mammary gland (L4, L5, R4 and R5) through intramammary route. Mice were sacrificed at 6, 12, 24, 48, 72 and 96 h, and blood and mammary gland tissues were collected for blood immunophenotyping and cytokine gene expression studies, respectively. CD4+ cells increased in S. aureus, S. epidermidis, S. haemolyticus and decreased in S. chromogenes inoculated mice. CD8 + cells increased in S. epidermidis compared to other groups. Proinflammatory cytokines showed increased expression of IL-1β (6 folds), IL-4 (3 folds), IL-6 (1 fold), IL-12 (5 folds), TNF-α (5 folds) and IFN-γ (2 folds) in S. aureus inoculated mice. S. epidermidis revealed 2 fold increase in IL-1β and IL-4, and 1 fold increase in IL-6, IL-12, TNF-α and IFN-γ. S. chromogenes showed increased expression of 2 folds in IL-1β, IFN-γ; 3 folds in IL-4, IL-6, TNF-α and 7 folds in IL-12. S. haemolyticus revealed 2 folds increase in IL-1β, IL-12, TNF-α; 3 folds in IL-6 and 5 folds in IL-4. Hence, S. aureus caused severe mastitis in mice when compared to three coagulase negative staphylococcal (CNS) species. The proinflammatory cytokines (IL-1β, IL-4 and IFN-γ) can be used as an indicator for early detection and mice can be used as mastitis model to study CNS mastitis.